The effect of original LG revenue, balancing fund, and capital expenditure on LG financial performance in regencies in East Java Province - Firmansyah Thalib; Diah Ekaningtias (STIE Perbanas Surabaya, 2019)
Local Government (LG) financial performance is the level of work achievement in regional finance which is assessed using the state financial system stipulated in the statutory provisions. This study aimed to examine the effect of original local government revenue, balancing funds, and capital expenditure on LG financial performance. It used the population of all regencies in East Java Province. They were taken using saturated sampling method. The secondary data consist of all audited LG financial statements of 29 regencies in East Java Province period 2013 – 2017. The data were analyzed using multiple linear regression analysis with SPSS 23. The results showed that original LG revenue and balancing funds have a negative and significant effect on LG financial performance, while capital expenditure has no effect on LG financial performance.